Financial Accounting Information System Mediates the Effect of Good Corporate Governance and Research Development Costs on Stock Price Crash Risk - Harmadji, Dwi Ekasari; Doloksaribu, Tio Arriela (IndoCompt Publisher, 2025)
Stock price crash risk is an important phenomenon in the capital market that can cause significant losses for investors. Good corporate governance and research & development costs are predicted to have an effect on stock price crash risk, but the mediating role of financial accounting information systems in this relationship has not been widely studied. This study aims to analyze the effect of good corporate governance and research & development costs on stock price crash risk with financial accounting information systems as mediating variables. This study uses a descriptive quantitative approach with a sample of 120 manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2024. Data were analyzed using SPSS version 23 with multiple regression analysis techniques and the Sobel test to test the mediation effect. The results showed that good corporate governance had a significant negative effect on stock price crash risk (β = -0.324, p <0.05), research & development costs had a significant negative effect on stock price crash risk (β = -0.287, p <0.05), and financial accounting information systems partially mediated the relationship between the two independent variables on stock price crash risk. Implementation of good corporate governance and investment in research & development can reduce the risk of stock price crashes, with financial accounting information systems acting as a mediator in this relationship.